Pengolahan limbah air rebusan ikan teri menjadi pupuk organik cair dan aplikasinya terhadap hasil tanaman bayam (Amaranthus sp.) - Siti Holifah (Fakultas Pertanian Universitas Yudharta Pasuruan, 2019)
Liquid waste decoction results that are wasted need to be utilized as a new product that is economically valuable so as not to pollute the environment, one of them by making organic water fertilizer (POC). The purpose of this study was to determine the impact of anchovy boiled liquid waste on the environment around the factory, knowing the right formulation in making liquid organic fertilizer and determine the effect of liquid organic fertilizer from anchovy boiled liquid waste on Spinach plants. The parameters of the pollution test were BOD, COD and pH, N, P, K, C organic and organoleptic. Observation parameters on the influence of POC on Spinach plants were Wet Weight and dry weight of the plant with an oven at 40 suhuC for 3 days. This study used a Completely Randomized Design (CRD) method, an experiment consisting of 1 factor, 5 liters of anchovy liquid treatment/treatment and 5 treatments, namely the concentration of EM4 with a combination of 5%, 10%, 15%, 20%, 25% levels. The results of this study indicate that the effluent of boiled anchovy has an effect on the environment around the factory. The right formulation in making liquid organic fertilizer from anchovy boiled water is the addition of 5% EM4. Liquid organic fertilizer from boiled anchovy water also affects the yield of Spinach (Amaranthus sp.) Because it can increase the dry weight value of Spinach plants.